The professionalization of English medium instruction lecturer: content and certification - Sun, Yi (Frontiers in Education, 2023)
This paper surveys the professional competence requirements and professional certification of English medium instruction（EMI) lecturers worldwide in order to inform decisions by researchers and administrators tasked with the design and delivery of the certification activity. The survey encompasses 38 articles which include information about EMI lecturer ability, professional development, and certification. The paper analyzed the content of them about competence components and delivery methods. The analysis reveals four main competence components: language, pedagogy, multi-culture, and EMI awareness. The certification in current can be divided into two categories depending on whether they include a training program. Certification that consists only of tests usually focuses more on the teacher's English proficiency in teaching. Another certification usually has the essential English requirement for the participants and pays more attention to the pedagogical methodology. The paper concludes with recommendations for the development of the EMI lecturer competence framework and certification program.